Do Banks Lend Less in Uncertain Times? - Burkhard Raunig; Johann Scharler; Friedrich Sindermann (Oesterreichische Nationalbank (OeNB), 2014)
We study the development of bank lending in the U.S. after four large jumps in uncertainty using an event study approach. We find that more liquid banks reduce lending less than banks with smaller liquidity ratios after a surge in uncertainty. Lending by smaller banks is also less responsive to increases in uncertainty. Banks with a higher capitalization ratio keep up lending to a greater extent, but the effect is only significant for banks which are not part of a multi-bank holding company. This heterogeneity across banks suggests that declines in bank lending following increases in uncertainty are partly the result of a reduced supply of bank loans.
Keywords: E44; E20; E30; 330; uncertainty; bank loan supply; event study; Risiko; Kreditgeschäft; Ereignisstudie; USA